2022
DOI: 10.2514/1.a35103
|View full text |Cite
|
Sign up to set email alerts
|

Federated Space Systems’ Trade-Space Exploration for Strategic Robustness

Abstract: Motivated by the growth of the commercial space economy and renewed focus on the disaggregation of military space systems, this work develops a method for conceptual design of federated satellite systems as a collaborative system-of-systems (SoS). Objectives seek to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Notwithstanding the aforementioned limitations, this research produced several important findings. Previous research in systems‐of‐systems with interactions characterized by the stag hunt game showed that strategically robust designs protect implementer utility and improve collaboration 12,13,29 . This study shows that strategically robust designs embodied as groundwater wells reduce collaboration in simulated canal irrigation systems with dynamics partly characterized by a commons dilemma.…”
Section: Discussion and Limitationsmentioning
confidence: 54%
See 4 more Smart Citations
“…Notwithstanding the aforementioned limitations, this research produced several important findings. Previous research in systems‐of‐systems with interactions characterized by the stag hunt game showed that strategically robust designs protect implementer utility and improve collaboration 12,13,29 . This study shows that strategically robust designs embodied as groundwater wells reduce collaboration in simulated canal irrigation systems with dynamics partly characterized by a commons dilemma.…”
Section: Discussion and Limitationsmentioning
confidence: 54%
“…Previous research in systemsof-systems with interactions characterized by the stag hunt game showed that strategically robust designs protect implementer utility and improve collaboration. 12,13,29 This study shows that strategically robust designs embodied as groundwater wells reduce collaboration in simulated canal irrigation systems with dynamics partly characterized by a commons dilemma. The result shows that the dynamics created by differences in payoffs between strategic contexts is an important consideration for system design.…”
Section: F I G U R E 1mentioning
confidence: 82%
See 3 more Smart Citations